Pengaruh Penyakit Komorbid pada Pasien Terkonfirmasi COVID-19 Terhadap Hasil Pemeriksaan Laboratorium Penanda Inflamasi - Apriani; Basuki Rachmad; Nuraddiyani Hidayah; Islakhun Ni'mah (State Islamic University of Sunan Ampel, 2022)
Inflammatory reactions play an important role in the pathophysiology of COVID-19. Levels of D-dimer, procalcitonin (PCT) and C-reactive Protein (CRP) are known to increase in response to an inflammatory reaction. Comorbid COVID-19 patients are often associated with severe conditions and do not survive. In handling COVID-19 patients with comorbidities, it is necessary to recommend specific laboratory examinations to make the actions given more effective and efficient and reduce costs and treatment time. This study aims to determine the effect of comorbid on the results of laboratory examination of inflammatory markers. The study was conducted in June – August 2022 at Siloam Lippo Village Hospital. Subjects and laboratory results were presented descriptively. Test the effect of comorbid and inflammatory marker parameters using a statistical regression test (a=0.5%). Statistical tests showed no significant effect on comorbidity on laboratory results of inflammatory markers D-dimer (P= 0.467) and PCT (P= 0.834). Comorbidities significantly affected CRP examination results (P = 0.002). In this case, it is necessary to prioritize all comorbid COVID-19 patients to have an early CRP examination to treat rapidly decreasing oxygen saturation, deep vein thrombosis and pulmonary embolism and death.